Physical activity assessment in the general population; validated self-report methods - Ignacio Ara (Nutrición Hospitalaria, 2015)
Self-reported questionnaires have been commonly used to assess physical activity levels in large cohort stu - dies. As a result, strong and convincing evidences that physical activity can protect health are widely recogni - zed. However, validation studies using objective measu - res of physical activity or energy expenditure (double labelled water, accelerometers, pedometers, etc.) indicate that the accuracy and precision of survey techniques are limited. Physical activity questionnaires could fail in estimating particularly non-vigorous physical acti - vity. They have a disproportionate focus on volitional type exercise (i.e. biking, jogging, and walking), while not capturing the activities of daily living and low to moderate intensity movements. Energy expenditure estimates from these data are not recommended. On the other hand, despite objective tools should be the measu - rement of choice to assess PA level, self-reported questionnaires remain valid, and have many advantages. i.e. low costs. These kind of recalls are designed and vali - dated for different age groups and provide value and important information, mainly about physical activity pattern. Future studies will require more precision and accuracy in physical activity measurement than those provided by traditional survey methods. We can conclude that probably a mixed approach that combines both the objective and subjective techniques involving novel devices and electronic capture of physical activity questionnaires will be more effective .